TULA-2 Deficiency Enhances Platelet Functional Responses to CLEC-2 Agonists - Kostyak, John C.; Mauri, Benjamin R.; Dangelmaier, Carol; Patel, Akruti; Zhou, Yuhang; Eble, Johannes A.; Tsygankov, Alexander Y.; McKenzie, Steven E.; Kunapuli, Satya P. (TH Open, 2018)
Platelet activation is essential for hemostasis. Central to platelet activation are the signals transmitted through surface receptors such as glycoprotein VI, the protease-activated receptors, and C-type lectin-like receptor 2 (CLEC-2). CLEC-2 is a HemITAM (hem-immunoreceptor tyrosine activation motif)-bearing receptor that binds podoplanin and signals through spleen tyrosine kinase (Syk). T-cell ubiquitin ligand-2 (TULA-2) is a protein tyrosine phosphatase that is highly expressed in platelets and targets phosphorylated Y352 of Syk. We wanted to determine whether TULA-2 regulates Syk phosphorylation and activity downstream of CLEC-2. To that end, we used TULA-2 knockout mice and wild-type (WT) littermate controls. We found that TULA-2 deficiency enhances the aggregation and secretion response following stimulation with an excitatory CLEC-2 antibody or the CLEC-2 agonist rhodocytin. Consistently, Syk phosphorylation of Y346 is enhanced, as well as phosphorylation of the downstream signaling molecule PLCγ2, in TULA-2 knockout platelets treated with either CLEC-2 antibody or rhodocytin, compared with WT control platelets. Furthermore, the kinetics of Syk phosphorylation, as well as that of PLCγ2 and SLP-76, is enhanced in TULA-2 knockout platelets treated with 2.5-μg/mL CLEC-2 antibody compared with WT platelets. Similarly, thromboxane production was enhanced, in both amount and kinetics, in TULA-2−/− platelets treated with 2.5-μg/mL CLEC-2 antibody. TULA-2 acts as a negative regulator of CLEC-2 signaling by dephosphorylating Syk on Y346 and restraining subsequent Syk-mediated signaling.
Keywords: platelets; thrombosis; thromboxane A2